Special education leadership building effective programming in schools - Bateman, David 1963-; Cline, Jenifer L. (New York Routledge, 2019)
"Integrating coverage of the most important knowledge base, research, and practice in the field, this book prepares educators for the challenging role of special education leader. Special Education Leadership provides leaders with tools to, review programs, implement special education law, and build special education programs that effectively supervise and support teachers. Grounded in theory, this book also includes best practices for day-to-day operations, such as issues of teaching and learning, personnel selection and evaluation, basic financial management, working with parent relations, mental health issues, and legal matters related to special education. Full of advice from practitioners, end-of-chapter questions, and coverage of emerging trends, this book helps prepare special education administrators and supervisors to survive the pressures of working with students with disabilities while supporting appropriate services and preventing litigation"--Provided by publisher.
Part One: Change agent -- Introduction / Verne Beffert -- Part Two: Compliance leader -- Laws and special education administration -- State monitoring and compliance / Doug Cox -- Discipline for students with disabilities -- Mental health for students with disabilities / Jessica Wery -- Working with parents / Elizabeth Harkins Monaco -- Grades and graduation for students with disabilities -- Progress monitoring / Amy Finn -- Finance for the special education administrator / Carrie Turner -- Part Three: Instructional leader -- Evaluating special education staff -- Aligning special education department initiatives to district mission / Rhonda Brunner and Wendy Kubasko -- Part Four: Collaborative leader -- The conflict continuum -- Meeting strategies and how to prevent due process hearings -- Current and emerging trends facing special education / Laura Matson.
Includes bibliographical references and index.
Keywords: Special education -- United States -- Administration; Educational leadership -- United States; School improvement programs -- United States; Special education -- Study and teaching -- United States; Special education -- Law and legislation -- United States; Students with disabilities -- Education -- United States